Associations of CDH1 germline variant location and cancer phenotype in families with hereditary diffuse gastric cancer (HDGC). Issue 6 (11th February 2019) - Lo, Winifred; Zhu, Bin; Sabesan, Arvind; Wu, Ho-Hsiang; Powers, Astin; Sorber, Rebecca A; Ravichandran, Sarangan; Chen, Ina; McDuffie, Lucas A; Quadri, Humair S; Beane, Joal D; Calzone, Kathleen; et al.
Abstract : Introduction: Hereditary diffuse gastric cancer (HDGC) is a cancer syndrome associated with variants in E-cadherin (CDH1), diffuse gastric cancer and lobular breast cancer. There is considerable heterogeneity in its clinical manifestations. This study aimed to determine associations between CDH1 germline variant status and clinical phenotypes of HDGC. Methods: One hundred and fifty-two HDGC families, including six previously unreported families, were identified. CDH1 gene-specific guidelines released by the Clinical Genome Resource (ClinGen) CDH1 Variant Curation Expert Panel were applied for pathogenicity classification of truncating, missense and splice site CDH1 germline variants. We evaluated ORs between location of truncating variants of CDH1 and incidence of colorectal cancer, breast cancer and cancer at young age (gastric cancer at <40 or breast cancer <50 years of age). Results: Frequency of truncating germline CDH1 variants varied across functional domains of the E-cadherin receptor gene and was highest in linker (0.05785 counts/base pair; p=0.0111) and PRE regions (0.10000; p=0.0059). Families with truncating CDH1 germline variants located in the PRE-PRO region were six times more likely to have family members affected by colorectal cancer (OR 6.20, 95% CI 1.79 to 21.48; p=0.004) compared with germline variants in other regions. Variants in the intracellular E-cadherin region were protective for cancer at young age (OR 0.2, 95% CI 0.06 to 0.64; p=0.0071) and in the linker regions for breast cancer (OR 0.35, 95% CI 0.12 to 0.99; p=0.0493). Different CDH1 genotypes were associated with different intracellular signalling activation levels including different p-ERK, p-mTOR and β-catenin levels in early submucosal T1a lesions of HDGC families with different CDH1 variants. Conclusion: Type and location of CDH1 germline variants may help to identify families at increased risk for concomitant cancers that might benefit from individualised surveillance and intervention strategies.